Pelatihan Teknologi Pemipih Purun sebagai Strategi Pemberdayaan Kelompok Usaha Pengrajin di Desa Tumbang Nusa: Training on Purun-Flattening Technology as a Strategy to Empower Artisan Business Groups in Tumbang Nusa Village - Saputra Adiwijaya; Siti Unvaresi Misonia Beladona; Fitriana Selvia; Meiyanti Ratna Kumalasari; Laila Zahra; Irvan Maulana Fiqih; Muhamad Arief Rafsanjani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Tumbang Nusa Village, Pulang Pisau Regency, Central Kalimantan, has natural resource potential in the form of purun (Lepironia articulata), which grows abundantly in peatlands, swamps, and along riverbanks. Purun has long been utilized by the local community as raw material for handicrafts such as mats, bags, wallets, and eco-friendly straws. However, the purun-flattening process, which is still carried out manually, creates several challenges, including lengthy production times, inconsistent fiber quality, and heavy physical burdens on artisans. This community service activity aimed to provide training on the use of purun-flattening technology for the